Daikon Radish Cultivation Guide for Florida - Mary Dixon; Guodong Liu (EDIS)
Daikon radish is a versatile vegetable crop in the mustard family. It produces a large, white, cylindrical fleshy root weighing up to 4-7 lb. Daikon radish is an especially common vegetable in Asia, particularly Japan, and it tends to be less spicy than other garden types of radish. This new 7-page publication of the UF/IFAS Horticultural Sciences Department provides a primer on cultivation of daikon in Florida, including sections on propagation, growing conditions, pests and diseases, and agricultural, culinary, and medicinal uses. Written by Mary Dixon and Guodong Liu. https://edis.ifas.ufl.edu/hs1370